2016
DOI: 10.1136/jnnp-2016-314408
|View full text |Cite
|
Sign up to set email alerts
|

Randomised feasibility study of physiotherapy for patients with functional motor symptoms

Abstract: Objective To determine the feasibility of conducting a randomised controlled trial of a specialist physiotherapy intervention for functional motor symptoms (FMS). Methods A randomised feasibility study was conducted recruiting patients with a clinically established diagnosis of FMS from a tertiary neurology clinic in London, UK. Participants were randomised to the intervention or a treatment as usual control. Measures of feasibility and clinical outcome were collected and assessed at 6 months. Results 60 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
194
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 27 publications
11
194
0
3
Order By: Relevance
“…In future pragmatic trials, we advise to use short, less time-consuming outcome measures without overlap in content and with less emphasis on psychological aspects. In this study and that of Nielsen et al ,16 the SF-36 physical domain was the most promising primary outcome, as this outcome correlated best with patients’ perceived change of symptoms.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In future pragmatic trials, we advise to use short, less time-consuming outcome measures without overlap in content and with less emphasis on psychological aspects. In this study and that of Nielsen et al ,16 the SF-36 physical domain was the most promising primary outcome, as this outcome correlated best with patients’ perceived change of symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, Lehn et al 15 reviewed the studies on treatment in FNS; using this review, we calculated that in total 468 patients were included in 10 randomised trials. After this review, another trial16 was published, making the total number of included patients 528.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised controlled trial (RCT) of 60 patients randomised either to specific FND therapy or a similar number of community physiotherapy sessions showed significant improvement in functional independence and mobility scores in the treatment vs control arms (72% vs 18%) even in patients with long duration of symptoms (5.8 years) 47. Patients in the control arm only improved in 18% of cases and on 6-month follow-up, 32% had developed worsening symptoms (3% in the treatment arm).…”
Section: Treatmentmentioning
confidence: 99%
“…Another Randomised Controlled Trial (RCT), also of 60 patients with functional gait disorder, demonstrated the normalisation of gait in most patients despite a 9-month duration of symptoms 48. More than half of the patients in Nielsen et al ’s 2016 study had pain or fatigue described as severe or extreme 47. Part of the treatment was education that the mechanisms for FND are similar to those for chronic pain, are not correlated with worsening structural damage and are potentially reversible by retraining.…”
Section: Treatmentmentioning
confidence: 99%
“…For example, encouraging and reinforcing normal function was an integral part of the intervention, as well as minimising the attention given to sickness or illness behaviours. An interesting feasibility study undertaken by Nielsen et al (2016) found that an organised targeted programme of physical rehabilitation taken over a 5-day period improved outcomes for patients with Functional Motor Symptoms compared to a non-standardised treatment programme. Just over three quarters of the patients rated their symptoms as improved compared to just 18% of the control group.…”
Section: Management Of Fnsdmentioning
confidence: 99%